Is there any role of reduction mammoplasty in decreasing breast cancer risk in gigantomastia? (Annals of Medical Research, 2022)
Aim: Large breasts create psychological and physical problems in women, all of whom must also keep in mind the common problem of breast cancer. In the present study we examine the effect of breast reduction surgery on breast cancer risk.Materials and Methods: Our retrospective study is based on the records (between June 1, 2014, and June 30, 2019) of patients who underwent breast reduction surgery in the Plastic, Reconstructive and Aesthetical Surgery clinic of a training and research hospital. Statistical analyses were conducted using IBM SPSS Statistics (Version 25.0. Armonk, NY: IBM Corp.). Normal distribution of the data was analyzed with Kolmogorov-Smirnov. The data assessment included descriptive statistical methods and Kruskal-Wallis test. The results were evaluated at a 95% confidence interval and a significance level of p
Keywords: Breast cancer; breast reduction surgery; retrospective analysis